2013
DOI: 10.1186/1472-6785-13-11
|View full text |Cite
|
Sign up to set email alerts
|

Age-related differences in the cloacal microbiota of a wild bird species

Abstract: BackgroundGastrointestinal bacteria play a central role in the health of animals. The bacteria that individuals acquire as they age may therefore have profound consequences for their future fitness. However, changes in microbial community structure with host age remain poorly understood. We characterised the cloacal bacteria assemblages of chicks and adults in a natural population of black-legged kittiwakes (Rissa tridactyla), using molecular methods.ResultsWe show that the kittiwake cloaca hosts a diverse ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
103
3
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(129 citation statements)
references
References 50 publications
(76 reference statements)
18
103
3
3
Order By: Relevance
“…The lack of differentiation between juvenile and adult community structures is an interesting finding, as strong differences have been reported for other avian systems in which the juveniles were of an age similar to (32,36) or older than (33) the juveniles studied here. Despite the lack of difference in community structure, some OTUs varied significantly in abundance between younger and older birds, likely reflecting at least some role of bird age in shaping the microbiota.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The lack of differentiation between juvenile and adult community structures is an interesting finding, as strong differences have been reported for other avian systems in which the juveniles were of an age similar to (32,36) or older than (33) the juveniles studied here. Despite the lack of difference in community structure, some OTUs varied significantly in abundance between younger and older birds, likely reflecting at least some role of bird age in shaping the microbiota.…”
Section: Discussionsupporting
confidence: 67%
“…Previous research into the development of the gut microbiota in other host species has shown that the microbiota of juveniles differs significantly from that of adults in both avians and mammals (32)(33)(34)(35)(36), although it is not clear whether this pattern is reflected in the kakapo (12). In many avian species, the juvenile microbiota is a dynamically changing community (37-39) that gradually develops toward the adult community structure (33,36), but the changes in microbiota as the subject ages vary by host. For example, chickens are enriched in Lactobacillaceae in the first week of life (38), while juvenile turkeys appear to harbor a large proportion of Clostridiales until around 10 weeks of age (39).…”
mentioning
confidence: 99%
“…However, the fact that bacterial communities in all gerbil groups have passed through similar seasonal changes suggest that these changes may not be linked to changes in the internal environment of the host. Other studies reported that microbial communities show high variability between host individuals, age groups and sexes and/or a relatively high temporal stability (Moran et al, 2005;Costello et al, 2009;Godoy-Vitorino et al, 2010;Oh et al, 2012;Yatsunenko et al, 2012;Faith et al, 2013;van Dongen et al, 2013;Kueneman et al, 2014;Leclaire et al, 2014). The lack of interindividual variations in the composition of bacterial communities in our study may result from the transmission of fleas between hosts via direct interactions, replacement of burrows or free dispersal (Krasnov, 2008).…”
Section: Mcfallmentioning
confidence: 36%
“…Nevertheless, because vector-borne microbes spend a part of their lives in the blood of the vertebrate host, it is important to consider also the internal environment of this host. For instance, microbes in the bloodsimilar to other microbes in the vertebrate gut, secretion glands, plumage, cloaca and skin-may be influenced by host species, diet, personality, body mass, sex, age and health status (see, for example, Alexy et al, 2003;Voigt et al, 2005;Fierer et al, 2008;Turnbaugh et al, 2009;Martin et al, 2010;Koenig et al, 2011;Muegge et al, 2011;Roeselers et al, 2011;Saag et al, 2011;Yatsunenko et al, 2012;Faith et al, 2013;van Dongen et al, 2013;Gavish et al, 2014;Kedem et al, 2014;Kueneman et al, 2014;Leclaire et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Host physiology has been shown to have an impact on the development of the gastrointestinal microbiota (32). It is also likely that age-related differences arise due to a number of other factors, including resource competition between bacterial species, shifts in the host's diet, or agerelated variation in the chemical and physiological state of the gastrointestinal tract (33). Broilers are harvested at a relatively young age, approximately 42 days posthatch.…”
Section: Resultsmentioning
confidence: 99%